2005
DOI: 10.1016/j.jcis.2005.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorescent silica-coated gibbsite platelets

Abstract: We describe the fluorescent labeling of gibbsite particles. Gibbsite particles are first stabilized with polyvinyl pyrrolidone. Subsequently the particles are covered with a silica layer in which a fluorescent dye is incorporated. Both fluorescein and rhodamine dyes have been used. The fluorescent labeling is applicable to gibbsite particles of various sizes. Particles are transferred to dimethyl formamide by vacuum distillation after dialysis. These particles are used for confocal scanning laser microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Unfortunately, the problem of aggregation was much more pronounced for the coating of rods. In the literature, aggregation is attributed to the presence of APS molecules on the surface of the silica particles . These decrease the stabilizing negative surface charge of the silica layer by its basic amino groups, resulting in less stable particles.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the problem of aggregation was much more pronounced for the coating of rods. In the literature, aggregation is attributed to the presence of APS molecules on the surface of the silica particles . These decrease the stabilizing negative surface charge of the silica layer by its basic amino groups, resulting in less stable particles.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 There appear to have been only few other studies of this particular model system however. [27][28][29][30] Polystyrene (PS) can be dissolved in DMF and here it is shown that the resulting polymer solutions are near to theta (Θ) conditions. Using two different silica sizes allowed q to be varied, while the electrical double layer thickness (κ -1 ) could be varied through the LiCl concentration.…”
Section: Introductionmentioning
confidence: 95%
“…The addition of LiCl allows the charge interactions to be screened. Such suspensions have been used previously as model hard spheres. , There appear to have been only few other studies of this particular model system however. …”
Section: Introductionmentioning
confidence: 99%
“…Coating of the obtained platelets with silica was done using a modified Stöber method as follows [34][35][36]. The platelets were dispersed in a 100 g/L aqueous solution of polyvinylpyrrolidone (Aldrich, 40 kg/mol).…”
Section: Methodsmentioning
confidence: 99%